The relationship between accounting conservatism and financial statements quality: Empirical Study of an External Auditor’s and Accountant Expert’s Sample in SidiBel Abbes Province - Aksa , Ahlem; Hallam , Zouaouia (Journal of Research in Finance and Accounting, 2021)
This study aims at findings of the relationship between accounting conservatism and financial statements quality. To achieve study goals we run an empirical study for a sample of External Auditor’s and Accountant Experts in Sidi Bel Abbes province. The results shown that some companies don’t rely on unconditional conservatism, the Pearson correlation test show the significant relationship at level 0.05 between accounting conservatism and financial statements quality. We concluded that the regression model find impact on the financial statements quality by 0.259% for the conditional conservatism, and 0.321% on the relevance and faithful representation of accounting information The regression model is acceptable and the R2=0.620 and significant at level 0.05.